Islam Nusantara - Siti Makhmudah (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2018)
Actually, Islam Nusantara is not something new. The term 'Nusantara' combined with 'Islam' is not only confirming a kind of name but also a character that shows the style or color of a heterogeneous entity. 'Islam Nusantara' is a result of a long struggle between religion and culture; between texts and contexts that complement each other so that Islam is friendly, inclusive and flexible born. Starting from history, this article tries to present an old discourse that re-emerged in 2015 along with the congressional meeting of two large organizations: NU and Muhammadiyah. The presence of this article is actually also to respond to accusations that the Nusantara Islam is only synonymous with the Nahdliyin so that the name 'Islam Nusantara' is considered a new name for Islam for traditionalists.